Advanced convolutional neural network for accurate detection of different facial expression - RHAMIE, NOOR ALIAH NATASSYAH; JAWAD, Dr. MOHAMMED SAEED (Applied Information Technology And Computer Science, 2023)
Facial emotions is an expression that people always express in their daily communication such as happy face, sad face, stress face, angry face and confuse face. However, in this covid-19, people cannot see each other and they are separated from family and friends. Thus, this situation can lead into depression and anxiety in some people. Therefore, there is a development of artificial intelligent solution for detection and classification of facial emotions. People can recognize others emotions and can detect whether they in problems or need help. Pipeline methodology is used as the methodology to develop this application. This application was developed in window platform, from the testing had been done it had success to detect and classify human facial expression into emotions. This application is expected to ease educators to identify students’ emotions so that they can undergo teaching and learning process successfully. It will also ease people to recognize other people’s facial expressions and emotions.